Se-methylselenocysteine inhibits inflammatory response in an LPS-stimulated chicken HD11 macrophage-like cell model through the NFKB2 pathway - Yao, Min; Wang, Binyu; Li, Zitong; Wu, Suqing; Zhao, Bingyu; Sun, Ning; Xiao, Huiping; Wang, Jianwu; Liu, Guoping; Huang, Tinghua (Frontiers in Veterinary Science, 2025)
Among the various sources of selenium supplementations, the Se-methylselenocysteine (SeMC) is a natural organic selenium compound that has been demonstrated to have multiple advantages in terms of metabolism efficiency and biosafety in animals. Nevertheless, the genome-wide impact of SeMC on gene transcription remains to be elucidated. In this study, we employed an LPS-stimulated chicken HD11 macrophage-like cell model to identify the principal transcription factors involved in transcriptome regulation responsible for SeMC treatment. RNA-seq identified 3,263 transcripts that exhibited a statistically significant differential expression between the SeMC-treated group and the control group and 1,344 transcripts that exhibited a statistically significant differential expression between the LPS + SeMC- and LPS-treated groups (FDR < 0.05, FDR > 1.5). The bioinformatic analysis identified six transcription factors (NFKB2, RFX2, E2F5, ETV5, BACH1, and E2F7) as potential candidate genes for transcriptome regulation in SeMC-treated HD11 cells. Subsequent experimental verification demonstrated that SeMC suppressed the inflammatory response in an LPS-stimulated chicken HD11 cell model via the TXN2—NF-κB pathway. The administration SeMC was observed to reduce the production of ROS as well as the transcription and translation of inflammatory cytokines in both cell culture and in vivo animal studies. One candidate pathway by which SeMC exerts its effects is through the targeting of the transcription factor, NFKB2, by selenoprotein TXN2. This study identified key transcription factors and revealed one of the potential mechanisms through which SeMC exerts its anti-inflammatory effects from the perspective of transcriptional regulation.